Effect of stance position on kick performance in taekwondo - Estevan, I.; Jandacka, D.; Falcó, C. (Journal of Sports Sciences, 2013)
In taekwondo, the stance position can potentially affect kick performance. The aim of this study was to analyse mechanical variables in the roundhouse kick in taekwondo according to three stance positions (0°, 45°, 90°). Nine experienced taekwondo athletes performed consecutive kicking trials in a random order according to these three relative positions of the feet on the ground. Measurements for the mechanical analysis were performed using two 3D force plates and an eight-camera motion capture system. The taekwondo athletes` reaction and execution times were shorter when starting from the 0° and 45° stance positions than from the 90° position (P < 0.05). Moreover, the ground reaction force was negatively correlated with execution time and positively with velocity of thigh and shank. Our results suggest that the stance position affects the execution technique of taekwondo athletes` kicks. It is suggested that athletes should not adopt the 90° stance position because it will not enable them to achieve the best performance in the roundhouse kick.